Colonial army and society in northern Nigeria - Ubah, C. N. (Kaduna, Nigeria : Baraka Press, 1998)
The book deals with the British colonial army on Northern Nigeria soil. The Nigerian Armed Forces of today are the descendants and successors of the British colonial army in Nigeria.
Includes bibliographical references (p. 369-373) and index.
opc 10/01/17
Loans
Keywords: Armies; Colonial army and society; Great Britain; Nigeria, Northern